2020
DOI: 10.3390/ijerph17082944
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Mobbing in Polish and Lithuanian Organisations with Regard to Corporate Social Responsibility

Abstract: The ‘mobbing’ phenomenon is regarded as the actions or behaviour referring to an employee or directed against an employee, comprising persistent and drawn-out harassment or intimidation of that employee. This phenomenon causes substantial negative workplace consequences, but, above all, one should stress the consequences for the victims, which are devastating. This has been observed in a variety of organisations, regardless of the sector and country. Given these facts, the purpose of this study was to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 73 publications
0
18
0
2
Order By: Relevance
“…The empirical study was conducted employing the questionnaire “Mobbing as a Psychosocial Stressor in the Organizations Accessing and Implementing Corporate Social Responsibility—MOB-CSR”. This instrument is valid and reliable [ 83 ]; correlation relationships between subscales show interconnectedness and statistically reliable relationships except for work content vs. environmental responsibility. The correlation relationships between the scales of the instrument, presented in Table 3 , show that despite the strength of Spearman’s correlation coefficient (i.e., strong, moderate strength, weak or very weak), statistically significant relationships were found between all scales ( p = 0.000).…”
Section: Methodsmentioning
confidence: 99%
“…The empirical study was conducted employing the questionnaire “Mobbing as a Psychosocial Stressor in the Organizations Accessing and Implementing Corporate Social Responsibility—MOB-CSR”. This instrument is valid and reliable [ 83 ]; correlation relationships between subscales show interconnectedness and statistically reliable relationships except for work content vs. environmental responsibility. The correlation relationships between the scales of the instrument, presented in Table 3 , show that despite the strength of Spearman’s correlation coefficient (i.e., strong, moderate strength, weak or very weak), statistically significant relationships were found between all scales ( p = 0.000).…”
Section: Methodsmentioning
confidence: 99%
“…Sometimes mobbing causes dysfunction of relationships between employees. As a result, negative consequences, including, inter alia, resignation of employees may appear (Vveinhardt & Sroka, 2020). Research conducted in different countries show that the consequences for victims may be devastating.…”
Section: Mobbingmentioning
confidence: 99%
“…Nevertheless, only a few articles examining workplace mobbing/bullying in the context of CSR were detected in the scientific research database (the search was performed in Web of Science, Sagepub, Springer, Ebsco). For example, it is noted that the implementation of the CSR agenda can reduce bullying and harassment, which encourage employees to leave the organization (Ram, 2018;Vveinhardt et al, 2018), but it has been found that the prevalence of mobbing was lower in CSR-implementing organizations, although the phenomenon was not completely eliminated (Vveinhardt & Sroka, 2020). In addition, Zhao et al (2020) has pointed out that a better understanding of stakeholders' motivation can have a positive effect in reducing corporate hypocrisy that is also reflected by tolerance to bullying.…”
Section: Mobbing and Social Responsibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The new environment might have a negative effect, such as mobbing or bullying, which is more prevalent in the public sector [41]. • It causes a so-called preselection and schemes whereby an organization only selects those applicants who demonstrate shared organizational values on personal traits and fit into its voluntary and involuntary turnover [29].…”
mentioning
confidence: 99%